Projeto árvore da vida para a preservação dos ambientes naturais - Oberherr, Andréa Diana; Costa, Vânia Medianeira Flores (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The removal of native vegetation and indiscriminate land fragmentation, has indicated thereduction of biomes and threatening their existence. Among other important tools to reverse thissituation and ensure the sustainability of natural resources necessary for human survival, wemention the non-formal environmental education. From this perspective the Municipal Center forEnvironmental Studies Sapiranga, organized the Árvore da Vida Project, which was implemented inMarch 2007 and attended by 200 students in May 2010. This study aimed to apply the Árvore daVida design and analyze their actions, to see how they would affect the perception of participantsregarding the conservation and sustainable use of natural resources. The results showed that theÀrvore da Vida Project was effective and efficient in promoting non-formal environmentaleducation, enabling the formation of the ecological and contributing to the establishment ofhabits and attitudes of conservationists and sustainable use of natural resources.